Company Financing, Capital Structure, and Ownership: A Survey, and Implications for Developing Economies - Sanjiva Prasad; Christopher J. Green; Victor Murinde (SUERF - The European Money and Finance Forum, 2001)
This paper critically surveys the key literature on corporate financing policy, capital structure and firm ownership in order to identify the leading theoretical and empirical issues in this area. The theoretical component of the survey attempts to reconcile competing theories of capital structure and appraises recent models which use agency theory and asymmetric information to explore the impact of managerial shareholdings, corporate strategy and taxation on the firm's capital structure. The empirical component focuses on univariate analyses as well as multivariate models of capital structure, and makes a comparison between theoretical predictions and empirical results. Implications are identified in terms of promising research ideas (PRIs) for further research. The bulk of the empirical research that we survey is concerned with the experience of a few western industrial countries, and the implications of this research are assessed accordingly. However, we also aim to draw out implications for new research in developing and newly industrialised countries with an expanding corporate sector.
Keywords: G32; 330; Financing policy; Capital structure; Firm ownership; Corporate fianance and development; Kapitalstruktur; Finanzierungstheorie; Prinzipal-Agent-Theorie; Eigentümerstruktur; Theorie